ChatGPT Practices: Finance and Banking Domain - Md Hassan; Shahnaz Parvin; Jahangir Siddikee (Journal of Business, Communication and Technology, 2024)
This paper reviews the practice of ChatGPT in the field of finance and banking through a natural language processing (NLP) system developed by OpenAI. We also discuss applications of ChatGPT in finance and banking, such as the detection of fraud, risk management, forecasting and analysis of the market, management of investments, chatbots for customer service, personal financial management, impact investing, and asset management along with its challenges, limitations and extremely encouraging future potentials. We also recommend taking necessary steps by the authorities to create and enhance ChatGPT-related legislation and regulations to avoid illegal and criminal offences. The paper concludes that ChatGPT will perform better and offer a better user experience for a variety of banking and finance sectors. It is worth remembering that in a relatively short period of time, ChatGPT has garnered significant attention from research, industry, and academia. This study will be helpful for policy makers, practitioners, and researchers.